Age-dependent NK cell dysfunctions in severe COVID-19 patients - Fionda, Cinzia; Ruggeri, Silvia; Sciumè, Giuseppe; Laffranchi, Mattia; Quinti, Isabella; Milito, Cinzia; Palange, Paolo; Menichini, Ilaria; Sozzani, Silvano; Frati, Luigi; Gismondi, Angela; Santoni, Angela; et al. (Frontiers in Immunology, 2022)
Natural Killer (NK) cells are key innate effectors of antiviral immune response, and their activity changes in ageing and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Here, we investigated the age-related changes of NK cell phenotype and function during SARS-CoV-2 infection, by comparing adult and elderly patients both requiring mechanical ventilation. Adult patients had a reduced number of total NK cells, while elderly showed a peculiar skewing of NK cell subsets towards the CD56lowCD16high and CD56neg phenotypes, expressing activation markers and check-point inhibitory receptors. Although NK cell degranulation ability is significantly compromised in both cohorts, IFN-γ production is impaired only in adult patients in a TGF-β−dependent manner. This inhibitory effect was associated with a shorter hospitalization time of adult patients suggesting a role for TGF-β in preventing an excessive NK cell activation and systemic inflammation. Our data highlight an age-dependent role of NK cells in shaping SARS-CoV-2 infection toward a pathophysiological evolution.